PEDAGOGICAL CONDITIONS OF SOCIAL ENTREPRENEURSHIP EDUCATION IN MASTER'S DEGREE'S TRAININGS FOR TEACHERS - Valery Shapovalov; Irina Igropulo; Marianna Arutyunyan (Вестник Северо-Кавказского федерального университета)
The article deals with the increasing role of social entrepreneurship as a socio-economic and organizational phenomenon, the impact of social entrepreneurship on the solution of social problems is presented. The main features of social entrepreneurship are described. The analysis offoreign programs of teaching social entrepreneurship, features of theory and technologies of teaching social entrepreneurship of various categories of students is presented. Presents the results of design and implementation of the educational program «Social Entrepreneurship in Education». The expected results of training are described, the functions of the educational program and pedagogical conditions of training of students of the master's degree's program in social entrepreneurship are characterized. The prospects for the development of the theory and technology of teaching students of the master's degree's program in social entrepreneurship are considered.